Spot-scanning proton therapy for targets with adjacent cardiac implantable electronic devices – Strategies for breast and head & neck cancer. (January 2022) - Stick, Line Bjerregaard; Lægdsmand, Peter Magnus Trock; Bjerre, Henrik Laurits; Høyer, Morten; Jensen, Kenneth; Jensen, Maria Fuglsang; Kronborg, Mads Brix; Offersen, Birgitte Vrou; Kronborg, Camilla Jensenius Skovhus
Highlights: Secondary neutron dose was calculated for pacemakers and implantable cardioverter defibrillators for patients with breast and head & neck cancer. Decision algorithms for selecting patients with targets adjacent to pacemakers and implantable cardioverter defibrillators for proton therapy were established. Eligibility for proton therapy depends on individual evaluation for some patients. The expected gain from proton therapy should outweigh the risk of device malfunction. Abstract: Background and purpose: Cardiac implantable electronic device (CIED) malfunctions can be induced by secondary neutron dose from spot-scanning proton therapy. A recent in-vitro study investigating secondary neutron dose to CIEDs up to 7 mSv per fraction found that exposure of secondary neutrons in this range was clinically manageable. This study presents decision algorithms proposed by a national expert group for selection of patients with breast and head & neck (H&N) cancer with CIEDs adjacent to target for proton therapy based on the 7 mSv threshold. Methods and materials: Ten patients with breast cancer and five with H&N cancer were included in the study. Five patients with breast cancer received photon therapy with CIED and proton plans were retrospectively created. The remaining patients received proton therapy without CIED and a worst-case position of a virtual CIED was retrospectively delineated. Secondary neutron dose was estimated as ambient dose equivalent H*(10) using Monte Carlo simulations. Results: For patients with breast cancer and with contralateral CIED, the secondary neutron dose to the CIED was below 7 mSv per fraction for CTV < 1500 cm 3 in 2 Gy fractions and CTV < 1000 cm 3 in 2.67 Gy fractions. The secondary neutron dose to the CIED was below 7 mSv per fraction for all patients with H&N cancer. Conclusions: Simulations of neutron exposure suggest that proton therapy is feasible for most patients with CIED adjacent to target. This forms the basis for decision algorithms for selection of patients with CIED for proton therapy.